Réformes éducatives sous le Front populaire et mise à l'épreuve des normes professionnelles et pédagogiques. Le cas du livret Fontègne - Jean-Yves Seguy (Nantes Université, 2019)
This article attempts to describe foundations and implementation of a tool of support of the teachers involved in the experiment of the "classes d'orientation", from 1937 till 1939: the livret Fontègne. This experiment, established at the instigation of the Secretary of the Front populaire, Jean Zay, had for objective to prepare the scholar guidance of the pupils from the observation of the aptitudes in the class. The livret Fontègne had to support of the teachers to have a frame leading them to spot these aptitudes. This approach supposed a new standard to teach, leading in principle to develop practices being inspired by principles of the new education, by putting the pupils in situations allowing them to express their aptitudes. This norm was confronted with the existing norm until then in the secondary education, arousing deep debates. The article suggests reporting the construction of this new norms and its confrontation in the former norms.